The association of Wnt-signalling and EMT markers with clinical characteristics in women with endometrial cancer - Ledinek, Živa; Sobočan, Monika; Sisinger, Damjan; Hojnik, Marko; Büdefeld, Tomaž; Potočnik, Uroš; Knez, Jure (Frontiers in Oncology, 2023)
Endometrial cancer is the most common gynaecologic malignancy in the developed world. Risk stratification and treatment approaches are changing due to better understanding of tumour biology. Upregulated Wnt signalling plays an important role in cancer initiation and progression with promising potential for development of specific Wnt inhibitor therapy. One of the ways in which Wnt signalling contributes to progression of cancer, is by activating epithelial-to-mesenchymal transition (EMT) in tumour cells, causing the expression of mesenchymal markers, and enabling tumour cells to dissociate and migrate. This study analysed the expression of Wnt signalling and EMT markers in endometrial cancer. Wnt signalling and EMT markers were significantly correlated with hormone receptors status in EC, but not with other clinico-pathological characteristics. Expression of Wnt antagonist, Dkk1 was significantly different between the ESGO-ESTRO-ESP patient risk assessment categories using integrated molecular risk assessment.